THE IMPACT OF THE DIGITALIZATION TRANSFORMATION ON THE ABSORPTION OF MANPOWER FOR GRADUATES OF THE SHARIA BANKING STUDY PROGRAM IN FEBI IAIN PONTIANAK - Nurma Sari; Eko Bahtiar; Vianisya Nurfiga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2022)
The purpose of this study is first to find out what skills graduates of Islamic banking study programs must have in order to be able to face the competition in the era of digitalization transformation, secondly to find out the impact of digitalization transformation on the workforce of graduates of the Islamic Banking study program. The research method used in this study is a descriptive method with a qualitative approach through a tracer study. The data collection is done by distributing questionnaires and interviews. Informants in this study found 53 respondents. From the results of the study, it was found that the skills of graduates of the Islamic Banking Study Program, Faculty of Economics and Islamic Business Pontianak in the aspect of integrity (ethics and morals, expertise based on the field of science, use of technology and information, communication skills and teamwork in teams are mostly good and very good. While the skills of graduates of the Islamic Banking Study Program of the Pontianak Islamic Economics and Business Faculty in the foreign language (English) aspect are still not good. Meanwhile, the digital transformation carried out by various sectors has an impact on the employment of graduates of the Sharia Banking Study Program, Pontianak Sharia Economics, and the Faculty of Business. The absorption rate for graduates of the Islamic Banking Study Program, Faculty of Economics and Sharia Business, Pontianak, both in the government and private sector and particularly in the banking industry sector, is still very small. Keywords: Transformation, Manpower Absorption, and Graduates of the Islamic Banking Study Program